2014
DOI: 10.1038/ncomms5217
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into SUMO chain recognition and manipulation by the ubiquitin ligase RNF4

Abstract: The small ubiquitin-like modifier (SUMO) can form polymeric chains that are important signals in cellular processes such as meiosis, genome maintenance and stress response. The SUMO-targeted ubiquitin ligase RNF4 engages with SUMO chains on linked substrates and catalyses their ubiquitination, which targets substrates for proteasomal degradation. Here we use a segmental labelling approach combined with solution nuclear magnetic resonance (NMR) spectroscopy and biochemical characterization to reveal how RNF4 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 57 publications
9
82
0
Order By: Relevance
“…Crystal structures of di‐ or tetra‐SUMOs should be regarded as snapshots that most likely do not represent the structure in solution. Indeed, NMR spectroscopy studies suggested high mobility for the SUMO subunits; however, it is not known if certain preferred conformations exist and how these are populated . Our ensemble FRET measurements report on the average of all of these possible conformations, and a conformation with the two fluorophores in close distance might dominate the overall FRET effect.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Crystal structures of di‐ or tetra‐SUMOs should be regarded as snapshots that most likely do not represent the structure in solution. Indeed, NMR spectroscopy studies suggested high mobility for the SUMO subunits; however, it is not known if certain preferred conformations exist and how these are populated . Our ensemble FRET measurements report on the average of all of these possible conformations, and a conformation with the two fluorophores in close distance might dominate the overall FRET effect.…”
Section: Resultsmentioning
confidence: 87%
“…They are connected by flexible linkers of about six and five residues at their N‐ and C‐terminal ends, respectively. This view is supported by crystal structures of defined SUMO‐2 di‐ and tetramers that display no detectable electron density for the linker region, as well as by NMR spectroscopy and small‐angle X‐ray scattering (SAXS) experiments . The binding of multi‐SIM ligands of RNF4 to SUMO‐2 di‐ and tetramers has been investigated by the same studies by means of NMR spectroscopy and SAXS, and represent the only structural studies for such complexes so far.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…STUbLs bind poly-SUMO chains noncovalently through their multiple SUMO interaction motifs (SIMs), which mediate their dimerization, a feature essential for their activity and the eventual polyubiquitination of both SUMO and its attached targets ( Fig. 1; Plechanovová et al, 2012;Xu et al, 2014). These polyubiquitinated proteins are then targeted for degradation by the ubiquitin-proteasome system ( Fig.…”
Section: The Sumo Conjugation and Deconjugation Systemmentioning
confidence: 99%
“…2a) [33,34]. These interactions are characterized by backbone hydrogen bonds to positions 33, 35, and 37 to primarily β-strand motifs (Figs.…”
Section: Introductionmentioning
confidence: 99%